2008
DOI: 10.1111/j.1439-0418.2008.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of entomopathogenic fungi from the soil and their pathogenicity to two fruit fly species (Diptera: Tephritidae)

Abstract: The occurrence of deuteromycetous entomopathogenic fungi was determined by examining 224 soil samples from 19 locations in three climatic zones of Mauritius. Three sites were sampled per location: one site under vegetables cultivation, one site under sugar cane plantation and one natural site each within 1 km of each other. Soil samples were baited with the waxmoth larvae Galleria mellonella L. and incubated in the dark at 15, 20, 25 or 30°C for 7, 14 and 21 days. Entomopathogenic fungi were isolated from 77 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 50 publications
1
33
0
8
Order By: Relevance
“…Si consideramos estos aspectos, se lograra mayor eficacia cuando se utilicen en el manejo de dichas plagas. Por otro lado, debemos de considerar que los insecticidas sintéticos aplicados ya sea asperjados o como cebos tóxicos para el control de moscas de la fruta, generan problemas de contaminación y efectos adversos sobre organismos no blanco (Troestchler 1984, Croft 1990, Purcell & Shcroeder 1996, por lo que cada vez hay mayor interés por el aislamiento y caracterización de nuevas cepas de hongos entomopatógenos para identificar aquellas con actividad biológica (Sookar et al 2008). Las tres cepas evaluadas resultaron patógenas a adultos de A. obliqua, por lo que deben ser evaluadas en condiciones de campo, ya sea contra adultos emergiendo a través del suelo tratado y/o mediante dispositivos que liberen conidios (e.g.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Si consideramos estos aspectos, se lograra mayor eficacia cuando se utilicen en el manejo de dichas plagas. Por otro lado, debemos de considerar que los insecticidas sintéticos aplicados ya sea asperjados o como cebos tóxicos para el control de moscas de la fruta, generan problemas de contaminación y efectos adversos sobre organismos no blanco (Troestchler 1984, Croft 1990, Purcell & Shcroeder 1996, por lo que cada vez hay mayor interés por el aislamiento y caracterización de nuevas cepas de hongos entomopatógenos para identificar aquellas con actividad biológica (Sookar et al 2008). Las tres cepas evaluadas resultaron patógenas a adultos de A. obliqua, por lo que deben ser evaluadas en condiciones de campo, ya sea contra adultos emergiendo a través del suelo tratado y/o mediante dispositivos que liberen conidios (e.g.…”
Section: Discussionunclassified
“…La patogenicidad de las diferentes cepas de hongos entomopatógenos contra moscas de la fruta (Tephritidae) ha sido poco estudiada y los resultados obtenidos son promisorios, por lo que se requiere explorar nuevas cepas (Quesada-Moraga et al 2006, Muñoz et al 2009, Sookar et al 2008. La caracterización patogénica se ha realizado contra las distintas fases biológicas del insecto, en Ceratitis capitata (Wied.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…The effectiveness and efficacy of biological control agents infields are not clear, therefore, they are required further assessment before field and IPM applications. (Sookar et al,2008) revealed that the pathogenicity of 5 local isolates of Beauveria bassiana pathogenicity applied through surface treatment of were highly efficient to control Bactrocera cucurbitae adults within five days when mortality percent ranged between (2-94%).…”
Section: Introductionmentioning
confidence: 99%